2020
DOI: 10.3892/ijmm.2020.4577
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane inhibits the proliferation and invasion of hepatocellular carcinoma cells through regulating the PTEN/Akt/GSK‑3β/β‑catenin signaling pathway by downregulating miR‑25‑3p

Abstract: Sevoflurane (Sevo) is one of the most frequently used volatile anesthetic agents in surgical oncology and has various effects on tumors, including inhibiting tumor growth, recurrence, and metastases; however, the molecular mechanisms are unknown. This study tried to investigate the influence of Sevo on hepatocellular carcinoma (HCC) cells and its possible mechanisms of action. The present study found that Sevo suppressed both the proliferative and invasive capabilities of both HCCLM3 and Huh7 cells in a dose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Then, PTEN inhibits Akt to enhance GSK-3β expression, leading to β-catenin signaling inhibition and a decrease in expression level of its downstream targets including c-Myc and MMP-9. 249 In addition to PTEN, MARCH1 can function as regulator of PI3K/Akt signaling in HCC. Exposing HepG2 cells to secalonic acid-F (SAF) is correlated with a significant decrease in MARCH1 expression.…”
Section: Beta-catenin and Hepatocellular Carcinomamentioning
confidence: 99%
“…Then, PTEN inhibits Akt to enhance GSK-3β expression, leading to β-catenin signaling inhibition and a decrease in expression level of its downstream targets including c-Myc and MMP-9. 249 In addition to PTEN, MARCH1 can function as regulator of PI3K/Akt signaling in HCC. Exposing HepG2 cells to secalonic acid-F (SAF) is correlated with a significant decrease in MARCH1 expression.…”
Section: Beta-catenin and Hepatocellular Carcinomamentioning
confidence: 99%
“…sevoflurane could restore the level of miR-29a and inhibit tumor progression by lowering the expression of long non-coding RNA KCNQ1 opposite strand/antisense transcript 1 (lncRNA KCNQ1OT1) (26), which led to the reduction of DNA methyltransferase 3 alpha (Dnmt3a) (25) and chromebox protein homolog 3 (CBX3) (26) in HCC cell lines. In vitro studies also suggested that sevoflurane-stimulated tumor cells exhibited higher level of phosphatase and tensin homologue (PTEN) and inactivation of phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt) signaling pathway (25,27), a crucial signaling in tumorigenesis (65). Also, in both cell lines and animal models experiments, researchers observed a correlation of increased level of miR-148-3p and decreased Rho-associated protein kinase 1 (ROCK1) after sevoflurane treatment (28), which might account for its antitumor property.…”
Section: Mechanisms Functions References Proliferation Apoptosis Inva...mentioning
confidence: 99%
“…Impairment of MMP-9 expression and regulation affects various dysfunctions, including tumorigenesis, and MMP-9 suppression can be targeted in anticancer therapeutics [ 108 ]. Anesthesia may affect MMP-9 expression [ 74 , 94 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ].…”
Section: Tumor Factors: Emt Hypoxia-inducible Factor-1α (Hif-1α) Matr...mentioning
confidence: 99%
“…Sevoflurane and desflurane reduced the invasion of colorectal and neuroglioma cancer cells through downregulation of MMP-9 [ 94 , 110 ]. Moreover, sevoflurane inhibited the proliferation and invasion of HCC cells through downregulation of MMP-9 [ 111 ]. Zhang et al showed that fentanyl inhibited tumor growth and cell invasion in colorectal cancer by downregulation of miR-182 and MMP-9 expression [ 112 ].…”
Section: Tumor Factors: Emt Hypoxia-inducible Factor-1α (Hif-1α) Matr...mentioning
confidence: 99%